Layanan Bimbingan Klasikal Dengan Metode Problem Based Learning Terhadap Pemahaman Bahaya Cyber Grooming - Handayani, Ajeng Sri (Jurnal Empati Bimbingan dan Konseling, 2025)
The purpose of this study was to determine the effect of classical guidance services using the problem based learning method on understanding the dangers of cyber grooming in class X students majoring in Software Development and Games at SMK Negeri 2 Semarang. This study used quantitative research, the Pre-Experimental method with the One-Group Pretest-Posttest Design model. The samples in this study were 36 students of class X PPLG 1 and 35 students of class X PPLG 2, taken using a saturated sampling technique. The data collection tool used is a cyber grooming scale. The results of the hypothesis test obtained tcount = 11.977, ttable = 2.032 with a significance level of 5% (0.05). This shows that tcount 11.977 ttable 2.032, so that the alternative hypothesis (Ha) is accepted at a significance level of 5%. So it can be concluded that the classical guidance service with the problem based learning method influences the understanding of the dangers of cyber grooming.